The Effect of Electronic Services Quality on Trust-Building in Online Customers of Tehran’s Brokerage Firms - ali asghar Sajedi far; Mohammad Rahim Esfidani; Mohammad Hosein Vahdatzad; Meysam Mahmoudi Azar (Journal of Information Technology Management)
In today's world, with the growth of electronic commerce, customer’s trust has become very important. Electronic services provide a unique opportunity for businesses to present new models of value creation to customers. The quality of electronic services has a considerable effect on customers’ mental judgments about services and plays an important role in building the trust in them. This article is trying to analyze the effect of electronic services quality of Tehran brokerage firms in building customers trust regarding the importance of their trust in these services. In order to accomplish the above-mentioned objective, a questionnaire has been designed and surveyed, aimed to provide a model to express the factors affecting trust, emphasizing the role of electronic service quality, perceived risk and perceived value. Gathering the data from 373 customers and using structural equation modeling to analyze, some suggestions have been presented in order to improve the electronic services quality of brokerage firms. The results show that, in brokerage firms, there is a positive and meaningful relation between electronic services quality and customers’ trust.